Expressing spirituality in palliative care: a narrative review - da Silva, Alessandra Ribeiro (2024)
End of life requires a comprehensive approach to relief physical, emotional, family and social pain, addressing spiritual issues as a way to ensure patients all sources of comfort. Given this scenario, this narrative literature review discusses the effects of spirituality/religiosity in palliative care. Based on a manual search for papers in the PubMed and Virtual Health Library databases, 11 articles wereselected for the review. The discussions were divided into three axes: spirituality of terminally ill patients, spirituality of health professionals and spirituality of family members. In conclusion, spiritual practices during the end of life and in coping with anguish are crucial both for patients and their families and for professionals.